Microstructure characterization of sustainable light weight concrete using trapped air additions. - Said Maaty; Ahmed Elshami; Fryal Kamel (Fracture and Structural Integrity)
Light-weight aggregate and trapped air additions (TAD) affect concrete performance and lead to the production of light-weight concrete (LWC). In this research, fourteen mixes were designed to study the effects of TAD type and content and pozzolanic material (PZ) type on the microstructure characterization of concrete. Aluminum powder (AP) and lightcrete (LC) were used as TAD with content equal to (0%, 0.25%, 0.50%, 0.57%). The PZ included silica fume (SF) and fly ash (FA) with a content equal to 10% of the weight of cement. Tests were performed for compressive strength, density, SEM, EDS, XRD, and TGA/DTG. The results show that compressive strength and density are reduced as TAD ratios are increased.